"Death of The New Republic": Discursive conflict between tech industry management and journalism's cultural value. (2nd November 2017) - Creech, Brian; Rooney, Shannon
Abstract : When The New Republic owner and Facebook founder Chris Hughes replaced the magazine's top editors in December 2014, it set off a round of vociferous commentary declaring "The Death of The New Republic ." Portrayed as a conflict between journalistic tradition and Silicon Valley values, changes at the magazine crystallized lingering anxieties about the future of journalism and its relationship to the demands of the market. This article examines commentary about changes at the magazine through the lens of metajournalistic discourse, arguing that the discourses analyzed established the means by which structural conditions and philosophical challenges in the journalism industry were rendered sensible to the broader public. Though acts of personalized blame and schadenfreude at the publication's supposed demise characterized much of the discourse, other texts worked to clarify the stakes in the conflict, ultimately creating the terms by which the conflict could be made sense of and its consequence articulated to the broader field of journalism.